Proceedings of the 8th International Conference on Tangible, Embedded and Embodied Interaction 2014
DOI: 10.1145/2540930.2540952
|View full text |Cite
|
Sign up to set email alerts
|

MimiCook

Abstract: Referring to documents is common when making things, but there is a difficulty caused by the gap between a written description and the actual context of making. For example, when cooking following a recipe, people may lose their current position in the recipe, misunderstand the required amount of ingredients because of complicated measuring units, or skip steps by mistake. We address these problems by selecting cooking as our domain. Our proposed cooking support system, MimiCook, embodies a recipe in a real ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 14 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Cooking ideas is a system that can detect ingredients via RFID sensors and suggest recipes and procedures via an interactive tabletop (Lebrun, Lepreux, Haudegond, Kolski, & Mandiau, 2014). MimiCook introduces a cooking support system that suggests a cooking procedure via augmented images projected over the tabletop, and the guidance changes to next steps in line with the user's progress (Sato, Watanabe, & Rekimoto, 2014). Another study evaluates the Cook's Collage, a system that tries to prevent users losing track of the cooking progress by implementing a visual summary of on-going cooking activity, working as a memory aid during the process (Tran, Calcaterra, & Mynatt, 2005).…”
Section: Cooking Assistantsmentioning
confidence: 99%
“…Cooking ideas is a system that can detect ingredients via RFID sensors and suggest recipes and procedures via an interactive tabletop (Lebrun, Lepreux, Haudegond, Kolski, & Mandiau, 2014). MimiCook introduces a cooking support system that suggests a cooking procedure via augmented images projected over the tabletop, and the guidance changes to next steps in line with the user's progress (Sato, Watanabe, & Rekimoto, 2014). Another study evaluates the Cook's Collage, a system that tries to prevent users losing track of the cooking progress by implementing a visual summary of on-going cooking activity, working as a memory aid during the process (Tran, Calcaterra, & Mynatt, 2005).…”
Section: Cooking Assistantsmentioning
confidence: 99%
“…Cooking support systems are popular applications for a domestic projector-camera system because cooking activities have high affinity with hands free that can be realized by projection. The support ranges from presenting step-by-step instruction on the kitchen table [8,29] to presenting the method of handling ingredients, e.g., cutting fish by projecting the direction of moving a kitchen knife [33]. In case of ironing, Suzuki and Fujinami investigated a system that presents instructions for effective ironing of a shirt for novice users based on activity recognition, in which the effectiveness of reducing wrinkles compared with a stepby-step manual instruction acquisition on a PC screen was confirmed; however, wrinkles were not sufficiently removed according to the reports from experts [32].…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have used projectors to support manual work, such as picking items [1], cooking [7], and so on [5]. Korn et al [3] showed that projected information is helpful for impaired persons in performing manual assembly work.…”
Section: Related Workmentioning
confidence: 99%